The Effects of Human Resources Competency, Accounting Information Technology Implementation and Motivation on Financial Statement Quality of Savings and Loan Cooperative in Banyumas Regency - Rizqy, Ghina; Primasari, Dona; Budiarti, Laeli (Soedirman Economics Education Journal, 2024)
This research aims to analyze whether there is an influence between (1) Human Resource Competency, (2) Accounting Information Technology Implementation, and (3) Motivation on the quality of the Financial statement of savings and loan cooperatives in Banyumas Regency. The data used in this research is primary data obtained from filling out questionnaires to the treasurer or the finance department and management of savings and loan cooperatives in Banyumas Regency. Savings and loan cooperatives are selected based on criteria using purposive sampling technique and obtained a total of 48 cooperatives that used as research samples. The results show that Human Resource Competence has a positive and significant effect on cooperative’s Financial statement quality. Likewise with the Implementation of Accounting Information Technology which has a significant positive effect on cooperative’s Financial statement quality. Meanwhile, the motivation variable has a negative effect on cooperative’s financial statements quality. The implications of this research for the ministry of cooperatives is to highlight the importance of providing training and education about digitalization of Financial statement and the digital economy to all management so that they can help cooperatives provide accurate and good financial statements and for cooperatives themselves to always support cooperative management to be actively involved in such training and education.